A discussion of Neolithic settlement patterns in Saudi Arabia and Bahrain during the Holocene Pluvial Period - Reeler, Claire; Āl Shaikh, Nabiel (Proceedings of the Seminar for Arabian Studies, 2015)
Neolithic settlement in Arabia has been modelled in various ways in the literature. Use of the Arabian landscape during the early to mid-Holocene has been argued to have been relatively circumscribed. In this paper we argue that a large number of Neolithic sites in Arabia have not been included in discussions in the literature to date, and that these sites provide information about a wider range of settlement site types and locations than previously discussed. There is some evidence to suggest that people used the landscape proactively throughout the Holocene and were able to access water in previously known locations into the historic period. The pattern of lacustrine deposits in both Saudi Arabia and Bahrain and their associated archaeological sites is a recurring one, and demonstrates a far wider use of the landscape during the Neolithic than hitherto discussed. The only exception is the central Rub c al-Khalï where evidence of lithics seems to be lacking.